PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, NET INTEREST MARGIN, LOAN DEPOSIT RATIO, DAN NON PERFORMING LOAN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SEKTOR PERBANKAN DIGITAL DI INDONESIA) - Susandi, Revi Arti; Hidayat, Taufiq (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to determine and examine the effect of capital structure, company size, net interest margin, loan deposit ratio, and non-performing loans on firm value. The population in this study is The Digital Banking sector in Indonesia is listed on the Indonesia Stock Exchange for the period 2016 – 2021. The purposive sampling technique was used in determining the sample in the study to obtain 5 digital banking companies. Data were obtained from secondary data on the annual reports of companies listed on the Indonesia Stock Exchange 2016 - 2021. The analytical technique used in this study is panel data analysis. The results of this study indicate that the capital structure proxied using CAR has a positive effect on firm value, then firm size, Net Interest Margin, Loan Deposit Ratio, and Non-Performing Loans have no effect on firm value. In research using this model, it shows insignificant results because the financial ratios of digital banking easily experience trust issues, such as during a pandemic, the share price soared because people believe digital stocks are immune from a pandemic crisis, but now the pandemic is over and digital banking stocks are starting to be abandoned by investors, the share price continues to decline.